Sleep Quality and Sleep Duration with CKD are Associated with Progression to ESKD - Yamamoto, Ryohei; Shinzawa, Maki; Isaka, Yoshitaka; Yamakoshi, Etsuko; Imai, Enyu; Ohashi, Yasuo; Hishida, Akira (Clinical journal of the American Society of Nephrology, 2018)
Shorter or longer sleep duration and poor sleep quality are risk factors for numerous cardio-metabolic diseases, cardiovascular disease, and mortality in subjects with normal kidney function. The association of sleep duration and sleep quality with health outcomes in patients with CKD remains uncertain. A 4-year prospective cohort study in 17 nephrology centers in Japan, the CKD Japan Cohort (CKD-JAC) Study, assessed an association of self-reported sleep duration and sleep quality, on the basis of the Pittsburgh Sleep Quality Index (PSQI) questionnaire, with incidence of ESKD in 1601 patients with eGFR 10-59 ml/min per 1.73 m using multivariable-adjusted Cox proportional hazards models. Baseline sleep duration and PSQI global score for the 1601 patients were mean±SD 7.0±1.3 hours and median 4 (interquartile range, 3-7), respectively. Poor sleep quality (PSQI global score ≥6) was common ( =588 [37%]). During a median of 4.0 (2.6-4.3) years of the follow-up period, 282 (18%) patients progressed to ESKD. After adjusting for age, sex, eGFR, urinary albumin excretion, smoking status, body mass index, history of diabetes and cardiovascular disease, systolic BP, blockade of the renin-angiotensin system, use of hypnotics, and Beck depression inventory score, both shorter (≤5 hour) and longer (>8 hour) sleep duration were associated with ESKD (adjusted hazard ratios [95% confidence intervals] for ≤5.0, 5.1-6.0, 6.1-7.0, 7.1-8.0, and ≥8.0 hours were 2.05 [1.31 to3.21], 0.98 [0.67 to 1.44], 1.00 [reference], 1.22 [0.89 to 1.66], and 1.48 [1.01 to 2.16]), suggesting a U-shaped relationship between sleep duration and ESKD. PSQI global score ≥6 was also associated with incidence of ESKD (adjusted hazard ratios [95% confidence intervals] for PSQI global score ≤5 and ≥6 were 1.00 [reference] and 1.33 [1.03 to 1.71]). Shorter (≤5 hour) and longer (>8 hour) sleep duration and poor sleep quality (PSQI global score ≥6) were associated with ESKD in patients with CKD.